Is there a link between treatments with exogenous corticosteroids and dog behaviour problems?. (5th November 2016) - Notari, L.; Burman, O.; Mills, D. S.
Abstract : Possible side effects of exogenous corticosteroids have been described in both humans and laboratory animals, with recent studies highlighting this issue in dogs. In this paper the behaviour of 345 dogs drawn from the caseload of a behaviour clinic based in the north of Italy between February 2012 and November 2014 were analysed. Possible relationships between dogs that received treatment with corticosteroids versus dogs that received treatment with drugs other than corticosteroids and positive or negative affective states, aggression towards people, other behaviour problems apart from aggression, occurrence of severe bites, and prescription of psychoactive drugs were initially assessed using a Pearson's chi‐squared test. Regression analysis was then performed in order to evaluate the best predictors of the investigated items. The goal of this retrospective survey was to investigate possible relationships between the affective states associated with the behavioural complaint of dogs and their previous history of treatment with corticosteroids. Results showed that a history of corticosteroid treatment was a significant predictor of a range of behaviour problems associated with negative affective state, but this result may be confounded by age‐related effects.